On multi-cell packet scheduling of LTE-A cellular networks: a survey of concepts related challenges and solutions - Madi, Nadim K. M.; Mohd Hanapi, Zurina; Othman, Mohamed; Subramaniam, Shamala (Asian Network for Scientific Information, 2014)
The upcoming generations of cellular networks are foreseen to deliver a ubiquitous access to the rapid growing volume of mobile users. Therein, a stunning key feature of LTE is the ability to adapt the advancement in Radio Resource Management entity which scales up its potential to deal with multi-transmission scenarios by employing novel multi-antenna techniques on eNBs. This survey come in place to enlighten the aforementioned notions and deeply investigates the principles and approaches of LTE/LTE-A packet scheduling that are adapted in either Dl or UL channels. The main purpose of the study is to come out with a preliminary conceptual design of an optimal scheduling techniques in multi-cell heterogeneous environment keeping in mind the effects of inter-cell interference on the model overall QoS. Finally, it is recommended that a wise packet scheduling model for multi-cell LTE-A should involve an optimal trade-off between several QoS parameters having in mind interference mitigation as a main concern. Whereby, performance features of the known LTE/LTE-A scheduling categories, opportunistic scheduling, ICIC and CoMP can be realized in a single model.